PENINGKATAN KETERAMPILAN MENULIS PUISI SISWA KELAS X IPS 2 SMA N 1 KALASAN DENGAN MEDIA AUDIOVISUAL MUSIKALISASI PUISI - Arda Sedyoko; Denik Wirawati; Pipit Ristiana Anggraini (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2023)
There are four language skills that must be mastered by students, namely (1) listening, (2) reading and viewing, (3) speaking and presenting, and (4) writing. One problem that arises in class X IPS 2 SMA N 1 Kalasan is that students do not have good skills in writing poetry. So, this classroom action research aimed to improve the poetry writing skills of class X IPS 2 SMA N 1 Kalasan with audiovisual media of poetry musicalization. This classroom action research has four stages in each cycle, namely (1) planning, (2) action, (3) observation, and (4) reflection. All of these stages are described in 3 learning cycles, namely pre-cycle, as well as cycle 1 and cycle 2 with treatment or action. Based on the research data that has been done, it can be concluded that the application of audiovisual learning media to musical poetry can improve students' poetry writing skills. This is evidenced by before the action, the percentage of students who completed learning to write poetry was only 21.9%. However, after the action, in cycle 1 as many as 56.1% of students completed. Moreover, in cycle 2 as many as 84.4% of students completed learning to write poetry. Keywords: writing poetry, audiovisual media, poetry musicalization, language skills